Randomized, Double-Blind, Placebo-Controlled, Safety and Immunogenicity Study of 4 Formulations of Anthrax Vaccine Adsorbed Plus CPG 7909 (AV7909) in Healthy Adult Volunteers - Hopkins, Robert J. (2013)
A new anthrax vaccine that could accelerate the immune response and possibly reduce the number of injections needed for protection would be desirable in a post-exposure setting. This Phase 1 study compared the safety and immunogenicity of 2 IM doses (Days 0 and 14) of 4 formulations of AV7909 (AVA plus CPG 7909) with 2 IM doses of BioThrax(®) (Anthrax Vaccine Adsorbed) and 2 IM doses of saline placebo administered on Days 0 and 14. A total of 105 healthy adults 18 to 50 years of age were randomized to 1 of 6 study groups: BioThrax (0.5 mL), AV7909 Formulation 1 (0.5 mL AVA + 0.5 mg CPG 7909), AV7909 Formulation 2 (0.5 mL AVA + 0.25 mg CPG 7909), AV7909 Formulation 3 (0.25 mL AVA + 0.5 mg CPG 7909), AV7909 Formulation 4 (0.25 mL AVA + 0.25 mg CPG 7909), or saline placebo (0.5 mL). All randomized subjects received at least 1 vaccination, and 100 subjects completed the trial. After 2 doses, mean peak normalized toxin neutralizing antibody responses (TNA NF(50)) in the AV7909 groups were higher than in the BioThrax group. Differences among the 4 AV7909 groups were not statistically significant. Subjects who received AV7909 reached peak titers on Day 28 vs. Day 35 in the BioThrax group. The most common adverse events (AEs) in the BioThrax and AV7909 groups assessed as related to vaccination were injection site reactions. Transient lymphopenia was observed after the first dose in each AV7909 group. Frequencies of injection site and systemic reactions recorded by subjects in diaries for 7 days after each injection were highest with AV7909 Formulation 1. No AEs of special interest (autoimmune events) were observed in the study. Further studies of doses and dosing regimens are planned to assess the immunogenicity and reactogenicity of AV7909.